Advanced glycation end products increase lipids accumulation in macrophages through upregulation of receptor of advanced glycation end products: increasing uptake, esterification and decreasing efflux of cholesterol. Issue 1 (December 2016) - Xu, Lei; Wang, Yi-Ru; Li, Pei-Cheng; Feng, Bo
Abstract Background Previous reports have suggested that advanced glycation end products (AGEs) participate in the pathogenesis of diabetic macroangiopathy. Our previous study have found that AGEs can increase the lipid droplets accumulation in aortas of diabetic rats, but the current understanding of the mechanisms remains incomplete by which AGEs affect lipids accumulation in macrophages and accelerate atherosclerosis. In this study, we investigated the role of AGEs on lipids accumulation in macrophages and the possible molecular mechanisms including cholesterol influx, esterification and efflux of macrophages. Methods THP-1 cells were incubated with PMA to differentiate to be macrophages which were treated with AGEs in the concentration of 300 μg/ml and 600 μg/ml with or without anti-RAGE (receptor for AGEs) antibody and then stimulated by oxidized-LDL (oxLDL) or Dil-oxLDL. Lipids accumulation was examined by oil red staining. The cholesterol uptake, esterification and efflux were detected respectively by fluorescence microscope, enzymatic assay kit and fluorescence microplate. Quantitative RT-PCR and Western blot were used to measure expression of the moleculars involved in cholesterol uptake, synthesis/esterification and efflux. Results AGEs increased lipids accumulation in macrophages in a concentration-dependent manner. 600 μg/ml AGEs obviously upregulated oxLDL uptake, increased levels of cholesterol ester in macrophages, and decreased the HDL-mediated cholesterol efflux by regulating the main molecular expression including CD36, Scavenger receptors (SR) A2, HMG-CoA reductase (HMGCR), ACAT1 and ATP-binding cassette transporter G1 (ABCG1). The changes above were inversed when the cells were pretreated with anti-RAGE antibody. Conclusions The current study suggest that AGEs can increase lipids accumulation in macrophages by regulating cholesterol uptake, esterification and efflux mainly through binding with RAGE, which provide a deep understanding of mechanisms how AGEs accelerating diabetic atherogenesis.